The Efforts to Increase Artistic Sensitivity of Unesa’s Art Education Students by Painting with Watercolor and Wax Media - Winarno Winarno; Hendro Aryanto (Humaniora, 2016)
Artistic abilities of students who had been enrolled in Arts Educations Department of UNESA, in general, were a lack in realizing artistic aspect. It created the problems in learning and teaching of art. The purpose of this research was to increase the students’ sensitivity in creating their work. One way to solve this problem was by doing the work as much as possible, but the results were not fully obtained. So far, there were no standardized guidelines to help the improvement of the work quality in term artistic achievement level. While it became a problem in learning, there was an effort to find a simple and effective way by mixed media watercolor paint and wax. The method in this research was the design of class action research, where the research was conducted in the learning process of each cycle. Every cycle consists of planning, implementation, observation, and reflection. The result of this research shows an increasing of artistic quality regarding practical grades of art. However, there are other alternatives must be sought to increase students’ ability to create, view, appreciate something that is artistic.